2019
DOI: 10.1038/s41598-019-51368-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of being watched on facial EMG and autonomic activity in response to another individual’s facial expressions

Abstract: We tested if facial reactions to another person’s facial expressions depend on the self-relevance of the observed expressions. In the present study (n = 44), we measured facial electromyographic (zygomatic and corrugator) activity and autonomic arousal (skin conductance) responses to a live model’s smiling and neutral faces. In one condition, the participant and the model were able to see each other normally, whereas in the other condition, the participant was led to believe that the model could not see the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
(54 reference statements)
2
13
0
Order By: Relevance
“…Our findings corroborate those of Hietanen et al 22 , who also reported greater ZM activation when participants viewed smiling expressions, compared to neutral facial expressions, if they believed that they were being watched. However, that study presented only static and not dynamic facial expressions; only smiling faces were included in the stimuli.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings corroborate those of Hietanen et al 22 , who also reported greater ZM activation when participants viewed smiling expressions, compared to neutral facial expressions, if they believed that they were being watched. However, that study presented only static and not dynamic facial expressions; only smiling faces were included in the stimuli.…”
Section: Discussionsupporting
confidence: 91%
“…In that study, the researchers designed a liquid crystal (LC) shutter system that switched between transparent and opaque to control the timing of participants' exposure to models who were making eye contact or averting their gaze in real time 21 . Their findings indicated that differences in ZM activity while viewing a static smiling versus a neutral facial expression were observed only when the participants believed that they were being watched by the model 22 . However, the implications of their EMG results were ambiguous because the ZM responses to smiles did not differ between conditions with and without beliefs about being watched.…”
mentioning
confidence: 99%
“…Participants also moved their face more during the Answer phase than during the Question phase. In line with previous studies, this indicates that participants used facial displays as social signals (Chovil, 1991b;Crivelli & Fridlund, 2018;Fridlund, 1991;Hietanen et al, 2019).…”
Section: Social Signalling In Typical Individualssupporting
confidence: 91%
“…Finally, we performed an exploratory analysis on participant facial motion. Previous studies have found that participants make more facial displays when they are being watched (Chovil, 1991b;Fridlund, 1991;Hietanen et al, 2019), suggesting a role for facial displays in communication (Chovil, 1991a;Crivelli & Fridlund, 2018). We tested whether typical participants move their face more when being watched, and while speaking compared to listening.…”
Section: The Present Studymentioning
confidence: 93%
“…The muscle activity related to the experimental trials was calculated as change scores by subtracting the baseline muscle activity from each 500-ms average value, and these values were then averaged across the 3000-ms post-stimulus time-window within each experimental condition. These procedures are standard procedures on the field (see Tassinary & Cacioppo, 2000) and we have been following them in our previous studies (e.g., Hietanen et al, 2018;Hietanen et al, 2019;Hietanen et al, 2020;Kiilavuori et al, 2021). The mean number of accepted trials in each condition was as follows: Clear lenses MdPd: M = 6.6; MdPa: M = 7.0; MaPd: M = 7.3; MaPa: M = 6.7; Dark lenses MdPd: M = 6.7; MdPa: M = 6.8; MaPd: M = 8.7; MaPa: M = 7.6.…”
Section: Physiological Measuresmentioning
confidence: 99%